2022
DOI: 10.1039/d2cp01450e
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity–low-temperature stability assessment of perovskite solar cells operating on simulated Martian surface conditions

Abstract: Immigration to Mars, which is expected to be mainly powered by photovoltaics, is one of the greatest dreams of humanity. However, the extreme temperature difference and high-energy cosmic radiation on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 41 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…Our study confirms temperature-dependent and intensity-dependent trends from previous studies 2,33,44 utilizing two distinct cell architectures from ANU and Caelux, while also performing radiation tests on the same cells to contribute to the limited literature on low-energy proton radiation tests for PSCs. 4,16 With the resulting large data set of measured PSC efficiencies, we predict how the ANU PSCs would perform relative to SOA cells in the context of a space mission to Jupiter (5.5 AU, −140 °C from Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study confirms temperature-dependent and intensity-dependent trends from previous studies 2,33,44 utilizing two distinct cell architectures from ANU and Caelux, while also performing radiation tests on the same cells to contribute to the limited literature on low-energy proton radiation tests for PSCs. 4,16 With the resulting large data set of measured PSC efficiencies, we predict how the ANU PSCs would perform relative to SOA cells in the context of a space mission to Jupiter (5.5 AU, −140 °C from Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Sun et al performed a LILT study on a triple-cation PSC device fabricated using a p-i-n architecture, which looked at simulated Martian surface conditions. 2 Their work showed long-term stability of PSCs operating in Martian surface conditions and noted that device performance was actually improved slightly after a simulated Martian day. 2 Sun et al also confirmed that low-temperature induced phase transitions could contribute to the self-elimination of intrinsic defect states, improving the device efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations